Identification and evaluation of learning disabilities the school team's guide to student success - Johnson, Evelyn S. 1969-; Clohessy, Anne B. (Corwin, a SAGE company, 2014)
Ensure that your students have the support they need! When it comes to designing instruction for students with learning disabilities, one size does not fit all -- and that's also true for identifying and evaluating learning disabilities. Theories and legislation aside, it's critical for your school team to have a comprehensive plan to make sure every child gets the right kind of attention--and no one falls through the cracks. This compelling, easy-to-use handbook guides general educators, special educators, administrators, and school psychologists through the eligibility and evaluation stages to ensure that students get the best services and interventions they need to be successful. You'll find: -- Guidance on what data to collect and how to collect it -- Strategies for combining RTI with a comprehensive ..
Keywords: Learning disabled children -- Identification; Learning disabled children -- Education; Response to intervention (Learning disabled children)